#TITLE_ALTERNATIVE# - (NIM : 12104089); Pembimbing : Dr. M. Zaki Mubarok,ST.,MT., KRISHNA
Recent investigation results show that some ion exchanger resins have greater adsorption capacity and better kinetics than activated carbon. In contrast to activated carbon, ion exchanger resins do not require thermal activation. In addition for metals recovery, the ion exchanger resins can be used for recovering free cyanide from tailing, thus reducing of the cyanides consumption. Adsorption of gold from cyanide solutions can be achieved with strong basic, weak basic and carbon-based resins. In this research, adsorption behavior of gold dissolved in cyanide solutions onto an activated carbon and some commercial ion exchanger resins has been investigated by means of bath adsorption isotherm tests. The goldbearing cyanide solution was obtained from Pongkor gold mining of PT. Antam, Tbk. Commercial activated carbon from Pongkor and three commercial resins from Lewatite were used in the investigations. Experimental results indicate that gold adsorptions onto activated carbon and three commercial resins follow both Langmuir and Freundlich isotherm models. Carbon-based resin of AF 5 exhibited the largest adsorption capacity followed by the strong basic resin of Monoplus MP 800, the weak basic resin of guanidine and the active carbon. The parameter of adsorption intensity obtained from Langmuir model for the earlier mentioned adsorbents in mg/g (gold/resin) are respectively 65.8, 48.8, 44.3 and 18.3. In contrast to weak basic of guanidine resin, the increase of pH decreased the recovery of gold for the adsorption with the AF 5 resins. The change of pH only slightly influences the gold recovery onto the strong basic resin of Monoplus MP 800. The increased of bed volume rate from 9,6 to 24 decreased the gold recovery in the column adsorption tests respectively for AF5 from 76% to 74% and MP 800 from 73% to 65%. Kinetics study reveals that the rates of gold adsorption onto weak basic and strong basic resins are dependent on the initial concentration of gold in solution. At lower gold concentration of about 4 to 6 ppm, the rates of gold adsorption are controlled by film diffusion, while at higher concentration of 8 to 12 ppm are controlled by particle diffusion. For the activated carbon and carbon-based of resin of AF 5, the rates of gold adsorption are controlled by first order kinetic model.